The body in performance: cultural mediation at the Blumenau Museum of Art - Peruzzo, Leomar (2020)
In this study we discuss the body in performance in a course of cultural mediation at the Blumenau Museum of Art. The art teachers from the region of Blumenau participated in a training course focused on aesthetic education and body. Performance art as an action that mobilizes the body was a medium of art creation and a trigger to the aesthetic experiences related to teachers' voices. Being hybrid and contemporary, this research has the theoretical support of Larrosa (2016), Duarte Jr. (2001), Josso (2007; 2012), Dias and Irwin (2013), Le Breton (2012), and Martins and Picosque (2012). From Art-Based Educational Research A/r/tography emerges to propose the intertwining of the identities of artist, researcher, and teacher. The theoretical and methodological support for the research and the creation of visualities are based on A/r/tography. The study has offered the Art Teachers the creation of art by means of performance and proposed the subversion of traditional ways of establishing cultural mediation in museum spaces. The main finding of the course was the expansion of possibilities for thinking about cultural mediation paths with a perspective focused on the body and its sensitive potentialities.